ORGANIZATION OF COMPETITIVE PRACTICE OF YOUNG FOOTBALL PLAYERS IN UKRAINE AND POLAND AT THE CURRENT STAGE OF DEVELOPMENT (Physical Culture and Sport: Scientific Perspective, 2023)
The article reveals ways of organizing competitions for young football players in Ukraine and Poland. The relevance of the research lies in the comparison of approaches to organizing (preparation for) football competitions for children held in Ukraine and Poland. In order to optimize this process in the practice of training young Ukrainian football players. The purpose of the work is to determine the common and distinctive features of the organization of competitive football practice for children 11-12 years old in Ukraine and Poland.The key components of competitive practice in children's football in Ukraine and Poland are compared. The common structural elements of both models are that both countries use similar fields, balls, goals, game formats and methods of conducting football competitions among children. The differences in the organizational schemes of tournaments in Ukraine and Poland are: the duration and number of matches, the duration of tournaments and the number of teams participating in them, the rules and regulations of competitions. At the same time, in Polish children's football, along with the Ukrainian one, a more pronounced trend towards taking into account the peculiarities of the development of the children's body during the planning and organization of tournaments is observed, which is reflected by lower loads on the children's body. Also, the fact that the competitions are organized in such a way as to contribute, first of all, to the improvement of the technical and tactical preparation of the players and the formation of positive motivation in them for training and competitive activities. Therefore, it is appropriate to state that by taking into account the positive foreign experience (features of training and conducting competitions for young football players) and its integration in Ukrainian children's football, it is possible to optimize the competitive practice of young Ukrainian football players and, accordingly, contribute to higher quality processes of preparation for competitions, avoiding negative moments of overload, fatigue, etc.
Keywords: football competitions (tournaments); football players (children) aged 11-12; Ukraine and Poland; method and format of holding